Protective Effects and Mechanisms of Action of Ulinastatin against Cerebral Ischemia-Reperfusion Injury - Lv, Bing; Jiang, Xiao-Ming; Wang, Da-Wei; Chen, Jing; Han, Dong-Feng; Liu, Xiao-Liang (Current Pharmaceutical Design, 2020)
Background: Cerebral ischemia-reperfusion injury is an extremely complicated pathological process that is clinically characterized by high rates of disability and mortality. It is imperative to explore some effective neuroprotective agents for its treatment. Ulinastatin is a protease inhibitor with anti-inflammatory and antioxidant activity. For the past few years, new studies of ulinastatin for the treatment of ischemic brain injury have emerged. Objective: We conducted a review to summarize the mechanisms of ulinastatin and analyze its neuroprotective action against cerebral ischemia–reperfusion injury. Methods: We reviewed and summarized pertinent reports published between 1993 and 2019 from PubMed, Web of Science, and Embaseby searching for the scientific terms ulinastatin, cerebral ischemia–reperfusion injury, neuroprotective, stroke, cardiac arrest, and brain edema. Results: The protective mechanisms of ulinastatin in the key steps of cerebral ischemia–reperfusion injury include inhibition of inflammatory response, oxidative stress, neuronal apoptosis, neuronal autophagy, and aquaporin- 4 expression as well as improvement in blood–brain barrier permeability. In addition, we provide a perspective on potential research directions and clinical safety. Conclusion: Ulinastatin seems to have the potential to alleviate cerebral ischemia–reperfusion injury. These findings may be valuable to further promote the research and development of drug candidates and provide novel and reliable references for rational drug use.
Keywords: cerebral ischemia–reperfusion injury